An empirical study of criminal sanction on trademark counterfeiting in China - Cai, Chuanzi (International journal of law, crime and justice, 2020)
Based on the empirical study of more than 800 criminal cases of trademark counterfeiting in China, this article finds that criminal sanctions of counterfeiting cases are below the statutory minimum of the law, and most courts do not calculate illegal business volumes or fines before making the decisions. For providing policy recommendations, this study, by regression analysis, further demonstrates that attorney arguments and courts calculation on business volume does associate with severer sanctions. This highlights the importance of precise court calculation in counterfeiting cases. Additionally, counterfeiters who should be sentenced to longer imprisonment are only receiving greater fines instead of longer imprisonment terms than those cases with less severity. Repeat offenders are not receiving significantly higher sanctions than first-time offenders. These findings suggest that criminal courts may have core considerations on specific case characteristics, and these characteristics have different effects on the decisions of fines and imprisonment.